Forms of Sequentiality in Contemporary English Poetry: Simon Armitage and Glyn Maxwell - Peter Hühn (Anglica. An International Journal of English Studies)
This article discusses the sequential devices which structure lyric poems. The sequentiality of poems is usually given little systematic attention to in poetry analysis. The main focus tends to be on speaker, imagery, theme and prosody. But a central aspect of the meaning of any poem is the manner in which the progression of the poetic utterance is organised. One such device, widely used in traditional and contemporary poetry, is the schema of the narrative. This article briefly sketches a theoretical approach to the description of the sequential extension of poetic texts and applies it to examples from the work of two prominent contemporary English poets, Simon Armitage, the present poet laureate, and Glyn Maxwell.